INTEGRATION OF ISLAMIC VALUES IN EDUCATION AND CLASSICAL GUIDANCE METHODS IN ENGLISH LANGUAGE TEACHING - Sophya, Ida Vera; Farida, Farida (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study aims to find out how Islamic values and classical guidance methods are integrated in English language teaching. The research was conducted at SMP N 2 Jati Kudus. The participants in the study were 40 students. The tutors involved came from BKI Kreatif FDKI IAIN as many as 10 people. This research is field research with a qualitative approach. The research data was collected by observation, interview, and documentation methods. The validity of the collected data was tested by the source triangulation method. Data that have been tested for validity and declared valid are then analyzed by the descriptive qualitative method of Miles and Huberman which consists of the stages of data reduction, data presentation, and conclusion drawn. The findings of the study show that the values of Islamic teachings and the classical guidance method can be integrated simultaneously in English language teaching. Students show a positive and open attitude with English tutoring which is characterized by their enthusiasm. The values of Islamic teachings taught to students are honesty, discipline, responsibility, courage, mutual respect and respect, obedience, and so on. Students are taught the habit of always giving thanks, praying before and after studying. The classical guidance method has proven to be effective in increasing students' motivation to learn and Islamic values will shape students' character according to Islamic teachings with high confidence.